If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1y + -5 = -9 Reorder the terms: -5 + -1y = -9 Solving -5 + -1y = -9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1y = -9 + 5 Combine like terms: -5 + 5 = 0 0 + -1y = -9 + 5 -1y = -9 + 5 Combine like terms: -9 + 5 = -4 -1y = -4 Divide each side by '-1'. y = 4 Simplifying y = 4
| 5(x-8)+x=6(x-8)+8 | | 11x+29y=-13 | | n+7n/5=72 | | 5x+15-4x=-6-12 | | 3/x=13/5x+2 | | 15w^3+14w^2-8w=0 | | -18-6k=6(1+2k) | | 17x=16x-24 | | 7(2x+3)=7 | | 5y+2(y-2)=7y-2(y-10) | | 17x=16x | | x/12=x/4-2 | | E=lR | | 44=-u+188 | | 18x+64=19x | | x/5=x/6-3 | | 0x^2-71x-9=0 | | 106=161-w | | 4x^2-13x+3x=0 | | (15/x)=((x^2)-7x+17) | | -v+111=202 | | 1/3+7/8+4/5 | | -x+279=208 | | 3x-6(x+1)=-3x+19 | | 21/5(-13/4p+5)=651/5 | | X(6x-3)=(6x+9)(x-8) | | -4(5y-7)-y=-2(y-5) | | x*y=630 | | x(2x+3)=4 | | 3(x-8)=9x | | 3x+9-2x=13 | | 4x^4-20x^2+16=0 |